The evaluation of the knowledge levels and attitudes of medical students who have accomplished obstetric and gynaecological diseases internship in a medical school about human papilloma virus vaccine [Bir tıp fakültesinde kadın hastalıkları ve doǧum stajını yapmış öǧrencilerin HPV aşısı hakkında bilgi düzeyleri ve tutumlarının deǧerlendirilmesi] - (:unkn) unknown (Gulhane Military Medical Academy, 2011)
AIM: Aim of the study was to determine medical school students' knowledge levels and attitudes who accomplished Obstetric and Gynecology clerkship in a medical school about HPV vaccination and intention to suggest HPV vaccine to their patients. METHOD: This descriptive study was carried out in a medical school among 166 medical students accomplishing their internship in the Obstetrics and Gynaecological Diseases Department. Study data had been collected by questionnaire which had three part and 30 question. The data were evaluated by descriptive statistics. RESULTS: Fifty five point four of the students stated that they felt informed about HPV vaccine, 72.9% of them stated that HPV was more serious for women. 95.8% of the participants thought they would suggest HPV vaccine to their patients and the most proposed group was adolescent girls (51.6%). 80.5% of students stated their possibility to suggest the vaccine would increase in case the vaccine would be free. The most important drawback points of the students in suggesting the vaccine to their patients were thinking high priced and not cost effectiveness of the vaccine (51.6%) and inducing unprotected, risky sexual intercourses (45.9%). CONCLUSION: In this study we determine the professional acception of HPV vaccine between students. Also we determine the most important factor in suggesting the HPV vaccine is the cost effectiveness of it.
Keywords: Attitude; HPV vaccine; Knowledge level; Medical school; Student